Burnout of Special Educators Serving Students With Emotional-Behavioral Disorders: A Longitudinal Study. (June 2022) - Brunsting, Nelson C.; Bettini, Elizabeth; Rock, Marcia L.; Royer, David James; Common, Eric A.; Lane, Kathleen Lynne; Xie, Fei; Chen, Aiai; Zeng, Fanyi
We examined changes in burnout across three timepoints in one school year, in a sample ( N = 230) of special educators serving students with emotional-behavioral disorders, in 15 school districts selected through stratified random sampling at the national level. Emotional exhaustion decreased at each timepoint in the school year and personal accomplishment increased from fall to spring. Latent growth curve modeling did not produce latent trajectories of burnout among teachers; however, cross-lagged panel structure equation modeling revealed that emotional exhaustion and personal accomplishment had both direct and indirect effects on depersonalization. Differences in burnout were significant by race/ethnicity but not by gender. Participants reported higher emotional exhaustion, lower depersonalization, and higher personal accomplishment than a national sample. We provide implications for researchers and practitioners.